Induced pluripotent stem cell-derived cardiomyocytes: A versatile tool for arrhythmia research - Sinnecker, Daniel; Goedel, Alexander; Laugwitz, Karl-Ludwig; Moretti, Alessandra (Circulation Research, 2013)
Induced pluripotent stem cells offer the possibility to generate patient-specific stem cell lines from individuals affected by inherited disorders. Cardiomyocytes differentiated from such patient-specific induced pluripotent stem cells lines have been used to study the pathophysiology of arrhythmogenic heart diseases, such as the long-QT syndrome or catecholaminergic polymorphic ventricular tachycardia. Testing for unwanted drug side effects or tailoring medical treatment to the specific needs of individual patients with arrhythmogenic disorders may become future applications of this emerging technology. © 2013 American Heart Association, Inc.
CRIS-Team Scopus Importer:2023-03-08
Keywords: catecholaminergic polymorphic ventricular tachycardia; disease modeling; long-QT syndrome; reprogramming